Implementation of Inclusive Education Management in Elementary Schools - Khodijah, Khodijah; Priyantoro, Dian Eka; Aryanti, Della; Erliana, Dwi Fani (Journal of Research in Islamic Education, 2025)
Every child or student has the right to an equal education in a conducive educational environment. However, the reality is that many factors do not support the implementation of this right, especially in the management of inclusive education related to children or students with special needs (ABK) who have physical, mental, social, or emotional differences that inevitably affect their learning methods and therefore require different treatment in accordance with their needs. Therefore, a deep understanding of the management and implementation of effective inclusive education is necessary, along with an awareness of the barriers and enablers for the implementation of inclusive education management in elementary schools. Based on the results of text reviews and relevant research, data analysis began by classifying the collected data according to the issues being studied, then analyzing it using content analysis. The results of the analysis and interpretation of the data were then summarized. The research results indicate that inclusive education management in elementary schools needs to be implemented optimally, in accordance with the management functions at each stage of its implementation, starting from planning, organizing/managing, implementing, and evaluating. The supporting factors include the commitment of the government, schools, and the community to implement effective inclusive education. The inhibiting factors are: the lack of Special Education Teachers (GPK) in elementary schools; a curriculum that is not yet relevant/appropriate for the needs of inclusive education; and limitations in facilities and infrastructure that support inclusive education services.